Synthesis of Salacca Peel Based Activated Carbons Using Microwave Induced ZnCl2 Activation - Arenst Andreas; Jessica Atin; Christiandi Arifin; Hans Kristianto (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2017)
In this research, snake fruit (salacca) peel based activated carbons were prepared by ZnCl2 activation using microwave heating method. By using microwave heating, it is expected that the energy consumption in the activation process will be more efficient than that obtained by conventional heating. The effects of mass ratio of snake fruit peel to ZnCl2 (1:2 and 1:4), microwave power (130 watt, 230 watt, 380 watt, 540 watt, and 700 watt), and microwave radiation time (5, 15, 20, and 25 minutes) on the characteristics of activated carbons were investigated in detail. Activated carbons with BET surface area of 1796 m2/g were obtained at mass ratio of snake fruit peel to ZnCl2 of 1:4, microwave power of 540 watt, and 25 minutes of radiation time. Activated carbons were then used for adsorption of Cu(II) metal ions with initial concentration variations of 100, 150, 200, 250, and 300 ppm. Isotherm models used were Langmuir and Freundlich. From adsorption process, it was found that Langmuir model fitted experiment data well, with maximum adsorption capacity of 1262.62 mg Cu2+/g activated carbons. Kinetic model that were studied were pseudo first order, pseudo second order, and intraparticle diffusion mechanism. It was found that kinetic data followed well the pseudo second order model.